Nanostructured Chemoresistive Sensors for Oncological Screening: Preliminary Study with Single Sensor Approach on Human Blood Samples - N. Landini; G. Anania; M. Astolfi; B. Fabbri; A. Gaiardo; S. Gherardi; A. Giberti; V. Guidi; G. Rispoli; L. Scagliarini; M. Valt; G. Zonta; et al. (Proceedings, 2019)
The demand for reliable devices to detect tumor biomarkers in human body is constantly increasing [...]